REGIONAL ASPECT OF COLLECTIVE ENTERPRISE: ISSUES OF SUPPORT AND DEVELOPMENT - Чечетова, Наталья; Колубай, Ярослав (SWorldJournal, 2022)
The article proves the need for development in the regions of the main subjects of collective entrepreneurship. It is substantiated that for the development of collective entrepreneurship it is necessary to implement appropriate organizational and econom